Implementation of the Rights of Suspects As Manifestation of the Principle of Presumption of Innocence at the Investigation Level - Syaqira, Andi Zahwa; Lestari, Sri; Ilham, Muhammad Azham (Faculty of Law, Universitas Muslim Indonesia, 2025)
This research aims to analyze the implementation of suspects' rights during the investigation process and to identify the challenges encountered in upholding the presumption of innocence principle. The research method employed in this study is an empirical method, consisting of primary data derived from interviews conducted at the Parepare City Police Office and secondary data obtained from document studies, including books, research journals, and legislation relevant to this research. The findings of this study indicate that the investigation process, which is expected to reflect the principle of the presumption of innocence, is often not optimal in practice. Some of the suspects' rights are not fully upheld, such as psychological pressure on the suspects and the right to legal certainty regarding their detention. Several factors influence the examination of suspects that fail to reflect the presumption of innocence principle, categorized into internal and external factors. These factors may compromise the principle in practice. Therefore, better training for investigators, supportive regulations, and a reduction in external pressures are needed to maintain the integrity of a fair legal process.